IMPLEMENTATION OF CORPORATE ENVIRONMENTAL RESPONSIBILITY IN INDIA: A POSITIVE STEP TOWARDS FULFILLING NATIONAL OBLIGATION OF THE SUSTAINABLE DEVELOPMENT GOALS - Saha, Sohom; Das, Pradip Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The environment is a global disquiet in the twenty-first century. Its amelioration has become the responsibility of the individuals, governmental and non-governmental organisations. In this context, corporate establishments also play a significant role as one of the world’s important stakeholders. To encourage the corporate sector to prioritise environmental improvement, the concept of ‘corporate environmental responsibility’ has been established. It is an advanced concept of corporate social responsibility, having relevance for the environment in India. It encompasses several environmental and societal factors that align with the United Nations’ Sustainable Development Goals. Considering the role of corporate environmental responsibility, this paper attempts to assess the sustainability of the initiative in India. Besides this, previous directives in this motion have been analysed to identify gaps and covering factors in this regard. This comes with several scopes of action and presents challenges in its implementation. Accordingly, several gaps in the existing directives and the Indian form of corporate environmental responsibility, as well as inconsistencies, have been identified, which need to be addressed to achieve better results.